PENGARUH SUPPORT TEAMWORK, DUKUNGAN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PONOROGO - Agti Pribatiwi; Sri Hartono; Sujiono (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to examine the influence of teamwork support, organizational support, and organizational culture on employee performance at the Population and Civil Registration Office of Ponorogo Regency. The sample of this study was all employees at the Population and Civil Registration Office of Ponorogo Regency. The method used in this study is a quantitative method. Data in this study were obtained through observation, interviews, library research, and distributing questionnaires to respondents. The population in this study were structural and functional employees who were actively involved in the public service and administration process at the Population and Civil Registration Office of Ponorogo Regency. The sample in this study amounted to 63 people using saturated sampling technique. The results of this study indicate that teamwork support, organizational support, and organizational culture have a positive and significant effect on employee performance at the Population and Civil Registration Office of Ponorogo Regency.